Anti‐alcohol liver disease effect of Gentianae macrophyllae extract through MAPK/JNK/p38 pathway. (9th October 2018) - Cui, Yulei; Jiang, Lei; Shao, Yun; Mei, Lijuan; Tao, Yanduo
Abstract: Objectives: The hepatoprotective effect of Gentianae macrophyllae root extract (GME) on alcoholic liver disease (ALD) was evaluated through ethanol induced ALD animal model. Methods: Mice were randomly divided into control normal group (10 mice), ethanol‐induced ALD model group (10 mice) and GME plus ethanol group (30 mice). Mice in model group were given intragastric administration with 50% (v/v) ethanol aqueous solution (200 μl for each) once daily for 19 days. Mice in control normal group received equal volumes of water. Mice in GME plus ethanol group were given intragastric administration with 50% (v/v) ethanol aqueous solution (200 μl for each) once daily at 10:00 a.m., after 1 h, mice in GME group sequentially were treated with 20, 40 and 100 mg/kg of GME by gastric gavage for 19 days. the average food and water consumed by the mice in every group were recorded every 2 days and body weight of every mouse in every group was measured every 2 days. Key findings: Results showed that GME significantly improved alcohol induced liver injury in a dose‐dependent manner. The impaired hepatic tissue structure was repaired and the collagen deposition declined after GME administration. Meanwhile, the level of malonaldehyde (MDA), Aspartate transaminase (AST) and alanine transaminase (ALT) (indicators of liver damage) in blood serum were significantly controlled by GME with a dose‐dependent manner, moreover, body weight and liver index were also improved after administration of GME. Pro‐inflammatory cytokines including MCP‐1, TNF‐α, IL‐1 and IL‐6 were detected through RT‐PCR and ELISA in experiment and GME can significantly inhibit the expression of TNF‐α, IL‐1 and IL‐6 but have no effect on MCP‐1. In order to explore the mechanism of GME on ALD, MAPKs pathway was examined and results indicated that GME attenuated ALD through inhibiting the phosphorylation of JNK and P38 and further suppressing the initiation of inflammation. Conclusions: GME attenuated ALD through inhibiting the phosphorylation of JNK and P38 and further suppressing the initiation of inflammation.